Mengupas Hubungan Sublim Manusia dengan Alam Melalui Karya Mariam Sofrina - Antonia Kristiana Dian Putri (FOCUS, 2021)
Protecting and ensuring nature is a choice and also a necessity for many people to protect their lives. Everyone is competing and fighting for a beautiful and well-maintained environment. However, the activities that are deployed with all their strength and determination by humans actually lead them to fall into the effort to improve nature and forget a root relationship between nature and humans themselves, namely sublimity. Through the reflection of works in the form of landscapes presented by one of the Indonesian artists, humans are able to be reintroduced to this sublime state to rebuild a full relationship with nature.